Peningkatan Keselamatan Lalu Lintas pada Ruas Jalan Phh Mustofa di Kota Bandung - Reza, Muhammad Akmal; Adhiatna, Tatang; Amirudin, Dede (Green Publisher Indonesia, 2024)
Jl. PHH Mustofa is an arterial road located in Bandung City. Jl. PHH Mustofa is a national road and functions as a primary arterial road (a road that connects primary areas to city or urban activity centers). It has a road length of 2,372 meters, divided into 4 segments, and has a 4/2 TT road type except for segment 4. Based on the results of the general report analysis of the Bandung City PKL Team Jl. PHH Mustofa is an accident-prone area and is a priority for handling it. The main factor causing accidents on Jl. Mustofa PHH is caused by human factors. Meanwhile, infrastructure factors such as poor road equipment, the condition of signs being covered by trees, and road geometrics not complying with Road Geometric Standards. Meanwhile, human factors are caused by high-speed vehicles, as well as drivers who are careless and less careful when driving. It is hoped that by making efforts to address the safety of these problems, it can reduce the number of traffic accidents and the severity of accident victims on the Jl. PHH Mustofa in Bandung City.